A histopathological and epidemiological study of urothelial carcinoma at a tertiary care centre in Peshawar, Pakistan - Saeed, Saria; Khan, Danyal; Faisal, Shah; Rauf, Fozia; Ali, Muhammad Owais; Rehman, Asif (Journal of the Pakistan Medical Association, 2024)
Bladder cancer is the ninth leading cause of death worldwide and 14th leading cause of death in Pakistan. The objective of this study was to determine the frequency of urothelial carcinoma in various age groups, its gender distribution, and grades. A total of 131 cases of urothelial carcinoma, received at Department of Pathology, Peshawar Medical College, Peshawar, between January 2017 to December 2022, were included in the study; of them 107 (81.6%) were males while 24 (18.3%) were females with a mean age of 62±13 years. The most common histological subtype was papillary urothelial carcinoma in 117(89.3%) cases, followed by Squamous and Glandular in 5(3.8%) cases. Majority of the urothelial carcinoma with high grade showed a statistically significant relation with muscle invasion (n=38, 50.66%). Males were four times more likely to have urothelial carcinoma while older age groups were more likely to have high grade urothelial carcinoma. Keywords: Carcinoma, Urinary bladder, Cancer, Neoplasm, Urothelial.